2016
DOI: 10.3390/ijgi5040040
|View full text |Cite
|
Sign up to set email alerts
|

Research Data Management Training for Geographers: First Impressions

Abstract: Abstract:Sharing and secondary analysis of data have become increasingly important for research. Especially in geography, the collection of digital data has grown due to technological changes. Responsible handling and proper documentation of research data have therefore become essential for funders, publishers and higher education institutions. To achieve this goal, universities offer support and training in research data management. This article presents the experiences of a pilot workshop in research data ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…In the 13 sources selected for synthesis, we found 14 key cases for analysis. Out of the 13 sources selected for synthesis, as outlined above, 9 of the selected sources had a single case study focus (Baker et al, 2016;Grootveld & Verbakel, 2015;Haddow, 2014;Helbig, 2016;Papadopoulou & Miller in Clare et al, 2019;Papadopoulou & Grabauskiene in Clare et al, 2019;Wittenberg et al, 2018;Southall & Scutt, 2017;Read et al, 2019). Out of the original 13, 2 of the selected sources covered multiple case studies (Bryant et al, 2018;Surkis & Read, 2015), while 2 of the sources dealt with the same case study (Tang & Hu, 2019;Shipman & Tang, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In the 13 sources selected for synthesis, we found 14 key cases for analysis. Out of the 13 sources selected for synthesis, as outlined above, 9 of the selected sources had a single case study focus (Baker et al, 2016;Grootveld & Verbakel, 2015;Haddow, 2014;Helbig, 2016;Papadopoulou & Miller in Clare et al, 2019;Papadopoulou & Grabauskiene in Clare et al, 2019;Wittenberg et al, 2018;Southall & Scutt, 2017;Read et al, 2019). Out of the original 13, 2 of the selected sources covered multiple case studies (Bryant et al, 2018;Surkis & Read, 2015), while 2 of the sources dealt with the same case study (Tang & Hu, 2019;Shipman & Tang, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Slavnic 67 reported that, in Sweden, there is a paradox, as there is infrastructure in place for arching and reusing data, but it is illegal to reuse them for projects other than those for which they were originally obtained. In countries like Germany, there are also challenges relating to copyright and legality 68 . Therefore, datasets might need to be subject to restricted access requiring patents, or other specific situations.…”
Section: Recognising Authorshipmentioning
confidence: 99%
“…RDM courses primarily fall into two types of instruction format: workshops, either as a standalone course or as a series of sessions (Clement et al, 2017;Goben & Nelson, 2018;Helbig, 2016;Peters, 2017;Southall & Scutt, 2017); or online courses, allowing for learning to take place as it is convenient (Furukawa et al, 2018;Rice, 2014;Si, Xing, Zhuang, Hua & Zhou, 2015) and whenever it becomes directly relevant to research practice (Ward & Freiman, 2011, p. 269). Graduate RDM courses delivered as lecture series by librarians are rarer (Corrall, 2012;Whitmire, 2015), and this format is too resource-intensive for implementation in our institutional context.…”
Section: Rdm Teachingmentioning
confidence: 99%